Odpowiedzi

2010-04-09T14:23:15+02:00
A)
2x-5y-6=0
3x-4y-2=0

2x-5y=6|:2
3x-4y=2

x=3+2,5y
3(3+2,5y)-4y=2
9+7,5y-4y=2
3,5y=-7
y=-2

x=3+2,5*(-2)
x=3-5
x=-2

spr:
2x-5y-6=0
2*(-2)-5*(-2)-6=0
-4+10-6=0
0=0


B)
3y+5x=0
3x+2y=4

5x+3y=0|:5
3x+2y=4

x=-0,6y
3*(-0,6y)+2y=4
-1,8y+2y=4
0,2y=4
y=20

x=-0,6*20
x=-12

spr:
3y+5x=0
3*20+5*(-12)=0
60-60=0
0=0



C)
7x+8y=9
5x+6y=7|:5

7x+8y=9
x=1,4-1,2y

7(1,4-1,2y)+8y=9
9,8-8,4y+8y=9
-0,4y=-0,8
y=2

x=1,4-1,2*2
x=1,4-2,4
x=-1

spr:
7x+8y=9
7*(-1)+8*2=9
-7+16=9
9=9
7 4 7